The effect(s) of mask alignment to p-n junction / Ahd Syarifuddin Mohd Helmi - Mohd Helmi, Ahd Syarifuddin (2010)
This project was a study about the effects of mask alignment to p-n junction. A p-n junction is a junction formed by joining the p-type and n-type semiconductor together in a very close contact. The term junction referred to the region of the boundary for both type of the semiconductor. Mask was a piece of paper that contain image that would covered the entire wafer. Photolithography process would transfer the image on the mask to the wafer surface. A computer aided design (CAD) system used in which designers can completely describe the selected patterns that was desired to be fabricated. The digital data produced by the CAD system then drives a pattern generator, which is an electron beam lithographic system that transfers the pattern directly to electron-sensitized mask. TURBO CAD was a suite of CAD software products for 2-dimensional design and drafting. By using this software, different kind of masks with different kind of dimensions and alignment mark would be produced. Dimensions of device were important for determining the goodness and reability of the mask design. Mask need to be precisely aligned with the original aligned mask or otherwise it cannot successfully transfer the designed pattern to the wafer surface, causing device and circuit failures. By using different design of masks, many type of p-n junction can be fabricated. From this project it shown that mask alignment was very important and gave bad effects to our devices. It can be observed that the dimension (length and width) of device on the mask design affect the doping process. The most suitable mask of all the masks that have been created was mask for sample 4. The significance of the mask dimension and mask alignment determined through its effects to the p-n junction.